An improved rdwt-based image steganography scheme using qr decomposition and human visual system - Ng, Ke Huey (2021)
Recent years have seen a rising trend in the use of intensive transmission of information via the internet. Data protection has become a fairly important issue due to the fast progress of information and communication technology and the huge increase in internet usage by sending and receiving data. Steganography becomes more and more important as many joined the cyberspace revolution that utilizes the information exchanging technology. While exchanging information via text is no longer secure, hiding a secret message in images has gained much popularity as it has larger hiding space and therefore, more difficult to notice the presence of hidden information. Hence, imperceptibility plays an important role in this case. Once the private or secret message is easily noticeable in a weak steganography system with poor imperceptibility, it defeats the original purpose and prompts to be attacked by intruders. This study introduces a hybrid RDWT-based image steganography system with QR decomposition and the human visual system. Compared to the spatial domain, transform domain is preferable because it provides better robustness when it comes to attacks such as geometric attacks and compression. RDWT allows embedding of the same-sized secret image into the cover image as compared to DWT that only offers half the embedding capacity of RDWT. It also solves the shift variance problem caused by DWT to avoid inaccuracy during the extraction process. QR decomposition has been incorporated into the proposed scheme because it helps to eliminate the false positive issue which usually occurs in schemes involving Singular Value Decomposition (SVD). This study also proposes to hide secret information based on the entropy values using the human visual system. The system considers both entropy values of cover image blocks and secret images blocks before embedding process begins. Secret image block with the lowest entropy value will be embedded into the cover image block with the lowest entropy value. The embedding process continues until all secret image blocks have been embedded into a cover image according to their corresponding entropy values, from the lowest to the highest value. The reason is that HVS is less sensitive to areas with low entropy value. This approach enhances the imperceptibility of the scheme by embedding information in cover image blocks with lower entropy values as they appeared to be less sensitive for HVS to notice the difference between stego image and cover image. By applying the human visual system, the proposed scheme managed to achieve high average PSNR value of 62.5628 dB by embedding secret image of sizes ranging from 32x32 to 512x512 using image block size ranging from 4x4 to 32x32. However, the proposed scheme has low robustness against attacks. As a conclusion, the proposed scheme has shown better result compared to previous work in terms of imperceptibility and image quality.